PENGARUH PENDEKATAN OPEN ENDED TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS IV SEKOLAH DASAR - Salamah Indah Wahyu Saputri (Program Studi PGSD STKIP PGRI Banjarmasin, 2020)
This study aims to determine the effect of an open-ended approach on the Thematic learning outcomes of grade IV SDN Oro-Oro Ombo Madiun City. This research is an experimental research using Quasi Experimental Design. The population in this study were all fourth grade students of SDN Oro-Oro Ombo with a total of 46 students and a sample of 23 students as the experimental class. Data collection techniques using documentation, observation and tests. With instruments in the form of syllabus, lesson plans, observation sheets and test questions. The data analysis in this study used the t-test. The results of this study indicate that the average value of the experimental class is higher than the control class as evidenced by the results of tcount = 7.953 ≥ t table = 2.015. So it can be concluded that there is an effect of an open-ended approach on the Thematic learning outcomes of grade IV SDN Oro-Oro Ombo Madiun City.